Sexualidad, cuerpo y duelo : experiencia clínica con mujeres diagnosticadas con cáncer ginecológico o de mama (2010)
ABSTRACT: Diagnosis with gynecological or breast cancer obliges patients to deal with organic and psychological consequences which are particular to an illness which affects parts of the body which are full of subjective and cultural significance. Based on the formalization of 15 years of clinical experience with patients who suffer from this illness, this article proposes a reflection within the framework of psycho-oncology, on the psychic effects that these types of cancer have on patients. Areas highlighted are the concepts of sexuality, body and grief, and based on these, the proposal is that these cancers and their treatment produce multiple losses which can bring about affective reconstruction and give a new meaning to life. In some cases, patients focus on pain as a way of not giving up what they have lost.